Transcriptomics-informed pharmacology identifies epigenetic and cell cycle regulators that enhance AAV production - Joshua Tworig; Francis Grafton; Kaylin Fisher; Markus Hörer; Christopher A. Reid; Mohammad A. Mandegar (Molecular Therapy: Methods & Clinical Development)
Recombinant adeno-associated virus (rAAV) is a widely used viral vector for gene therapy. However, these vectors have limited availability due to manufacturing challenges with productivity and quality. These challenges can be addressed by better understanding the mechanisms that influence cellular responses during rAAV production. In this study, we aimed to identify targets that may enhance rAAV production using transcriptomic analyses of five cell lines with variable capacities for rAAV production. Using an intersectional approach, we measured the transcriptional responses of these cells during rAAV production and compared transcriptional profiles between high and base producers to identify possible targets for enhancing production. During rAAV production, we found transcriptional differences in cell cycle and nucleosome components contributed to proliferative capacity and DNA replication. We also saw upregulation of several core functions, including transcription, stress response, and Golgi and endoplasmic reticulum organization. Conversely, we saw consistent downregulation of other factors, including inhibitors of DNA-binding proteins and mitochondrial components. With a drug-connectivity analysis, we identified five classes of drugs that were predicted to enhance rAAV production. We also validated the efficacy of histone deacetylase and microtubule inhibitors. Our data uncover novel and previously identified pathways that may enhance rAAV production and quality to expand availability of rAAV for gene therapies.